Genital scabies: Haven of an unwelcome guest - Gopinath, Hima (Indian J Sex Transm Dis AIDS, 2020)
The itch mite Sarcoptes scabiei var. hominis has been a menace to humanity for ages. Diagnosing scabies can be a challenge in view of the varied presentations of the disease. The male genitalia are an important area of predilection of the mite. Examination of this often overlooked area is essential as it may reveal both characteristic and atypical manifestations of scabies. Genital involvement also attains special relevance in view of the possible sexual transmission of the mite. In addition to the morbidity caused by itching, patients may have to deal with myths, stigma, and embarrassment.